Recuperação de populações de gastrópodes marinhos e costeiros após contaminação por COE's: um estudo de caso com Stramonita brasiliensis na costa do Ceará - Gomes, Jéssika Pereira (2024)
Populations of organisms inserted in contexts where there is the presence of impacts that affect one or more stages of their life cycle can take years to recover from low abundance due to their life history characteristics, the complexity of the ecosystem and the dimension of the disturbance. The present study aims to survey the recovery process of marine and coastal gastropods affected by contamination events through a literature review and a case study with the species Stramonita brasiliensis on the coast of Ceará. For the literature review, scientific articles published between 1990 and 2023 were selected in the Google Scholar database using the words contamination AND recovery AND population AND gastropoda with the selected works separated by year, country, authorship, species and contaminant. In total, 20 monitoring works from 13 species, ten countries and four contamination contexts were discussed. Among the studies analyzed, a majority were observed on the recovery of populations from contamination by organic tin compounds (80%) using the species Nucella lapillus (57%). Overall, it was observed that the species recovery capacity is directly linked to the reduction of exposure to the contaminant. For the case study using the species S. brasiliensis, 13 sampling stations were pre-determined according to the species monitoring history in the literature. At each station, the organisms were collected manually, measured (shell length and width) and returned to the environment. In areas where there was a possibility, 20 reproductive capsules were collected for egg counting in the laboratory. To monitor contamination levels, 30 adult individuals were removed from selected stations for laboratory analysis. The data obtained was spreadsheeted in Excel and statistical analyzes were carried out in R, based on the calculation of size class distribution, relative frequency and sexual maturation size (L50). The results of the analyzes are related to those found in the literature for other species, with S. brasiliensis showing clear signs of population recovery where it was possible to attest to a reduction in contamination levels.